A new hierarchical interconnection network for future generation parallel computer - Awal, Md. Rabiul; Rahman, M.M. Hafizur; Akhand, M.A.H (Institute of Electrical and Electronics Engineers Inc., 2014)
A Midimew connected Mesh Network (MMN) is a MInimal DIstance MEsh with Wrap-around links network of multiple basic modules, in which the basic modules are 2D-mesh networks that are hierarchically interconnected for higher-level networks. In this paper, we present the architecture of the MMN, addressing of node, routing of message, and evaluate the static network performance of MMN, TESH, mesh, and torus networks. It is shown that the MMN possesses several attractive features, including constant degree, small diameter, low cost, small average distance, moderate bisection width, and high fault tolerant performance than that of other conventional and hierarchical interconnection networks. It is also shown that with the same node degree, arc connectivity, bisection width, and wiring complexity, the diameter and average distance of the MMN is lower than that of the TESH network.